2004
DOI: 10.1038/sj.emboj.7600278
|View full text |Cite
|
Sign up to set email alerts
|

Sequential phases of cortical specification involve Neurogenin-dependent and -independent pathways

Abstract: Neocortical projection neurons, which segregate into six cortical layers according to their birthdate, have diverse morphologies, axonal projections and molecular profiles, yet they share a common cortical regional identity and glutamatergic neurotransmission phenotype. Here we demonstrate that distinct genetic programs operate at different stages of corticogenesis to specify the properties shared by all neocortical neurons. Ngn1 and Ngn2 are required to specify the cortical (regional), glutamatergic (neurotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
389
1
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(429 citation statements)
references
References 36 publications
22
389
1
10
Order By: Relevance
“…Pax6 marks a population of radial glial progenitor cells (Gotz et al, 1998) fated for glutamatergic differentiation (Schuurmans et al, 2004). Pax6 antibody staining revealed no overlap between Pax6 expression in the VZ and GFP expression in the SVZ and MZ, suggesting that the transgene was not prematurely activated ( Fig.…”
Section: Gfp Expression Within the Cnsmentioning
confidence: 96%
“…Pax6 marks a population of radial glial progenitor cells (Gotz et al, 1998) fated for glutamatergic differentiation (Schuurmans et al, 2004). Pax6 antibody staining revealed no overlap between Pax6 expression in the VZ and GFP expression in the SVZ and MZ, suggesting that the transgene was not prematurely activated ( Fig.…”
Section: Gfp Expression Within the Cnsmentioning
confidence: 96%
“…In the cerebral cortex, increased generation of upper-layer neurons after a temporary reduction in midstage neurogenesis occurs in cyclindependent kinase inhibitor p27 kip1 knockout mice (Goto et al, 2004), and the generation of glutamatergic deep-layer neurons is supported, whereas that of GABAergic neurons is suppressed, by Ngn1 (neurogenin homolog 1) and Ngn2 basic helix-loop-helix (bHLH) transcription factors (Schuurmans et al, 2004). Therefore, the timing of cell-cycle exit and the expression of transcription factors are important processes in the generation of deeper-layer neuron progeny.…”
Section: S-phase-dependent Responsiveness Of Progenitors To Bdnfmentioning
confidence: 99%
“…The expression of intrinsic cues such as neurogenetic transcription factors (Hevner et al, 2001;Schuurmans et al, 2004) and spatiotemporally regulated cell-cycle regulators (Caviness et al, 2003) have been suggested to specify the deeplayer cortical neurons. Neural progenitors in earlier stages can generate upper-layer neurons when such progenitors in S-phase are transplanted into older host brains; however, progenitors that have already passed through S-phase generate neurons that are committed to the original deep-layer fate (McConnell and Kaznowski, 1991;Desai and McConnell, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We first explored markers of early multipotential stem/progenitor cells: Pax6 , Emx2 (Heins et al, 2001), and Sox1-3 (Bylund et al, 2003). We then investigated transcription factors which are known to be specific for region-or lineage-restricted forebrain precursors: dorsal telencephalic markers such as neurogenin (Ngn) proteins (Schuurmans and Guillemot, 2002;Schuurmans et al, 2004), and ventral telencephalic markers such as Dlx (Anderson et al, 1997;Letinic et al, 2002;Stenman et al, 2003;Perera et al, 2004) and Olig (Schuurmans and Guillemot, 2002;Rowitch, 2004) proteins (Fig. 1).…”
mentioning
confidence: 99%